Physically-based extraction methodology for accurate MOSFET degradation assessment. Issue 9 (August 2015) - Torrente, Giulio; Coignus, Jean; Renard, Sophie; Vernhet, Alexandre; Reimbold, Gilles; Roy, David; Ghibaudo, Gerard
Abstract: This paper analyzes conventional parameter extraction methodologies applied to MOSFET devices subject to electrical stress and highlights the complexity to accurately get and separate both electrostatic and transport degradations. It is shown that an accurate Coulomb scattering assessment from the linear Id-Vg characteristics is mandatory whenever the amount of interface charges/traps becomes significant. Thus, this paper proposes a novel technique able to extract the electrostatic drift and the field-dependent mobility directly from the experimental data without any a priori assumption for the transport. Applied to MOSFETs experiencing Hot Carrier Stress, the proposed methodology provides deeper insights into the relationship between stress-induced defects location and their impact on electrostatic and transport degradations. Highlights: Conventional extractions applied for degraded MOSFETs via HCI have been explored. The complexity to accurately extract the aging through IdVg has been underlined. We propose a novel method that extracts easily electrostatic and transport drifts. Deeper insights into the electrical impact of the trap location have been addressed.